Open Access Publication of Universiti Sains Malaysia: a Bibliometric Analysis - Ismail, Mohd Ikhwan; Napiah, Mohd Kamal Mohd; Saad, Siti Roudhah Mohamad; Jaafar, Cik Ramlah Che; Azmi, Noor Adilah; Ahmad, Rosnani; Basri, Jamilah Hassan; Ahmat, Muhammad Akmal; Sultan, A. Basheer Ahamadhu Ameer; Jasni, Farah Aisyah; Khairuddin, Nur Afifa; Al-Munawar, Farah NurLiyana Ahmad (2017)
Open Access (OA) is the new publishing model that allows unrestricted access and reuse of research outputs. OA accelerates discovery in the sense that researchers can freely read and build on new findings based on other research. While public seems to welcome more involvement in OA among academics, many researchers are still discussing about the challenges that they face to publish with OA journals including the issue of article processing charge (APC) and the quality of OA journals. This paper examines several aspects relate to OA publication such as publication productivity, citation impact, subject coverage, and publishing cost of Universiti Sains Malaysia (USM) based on SCOPUS data from 2013 to 2015. The findings show that School of Medical Sciences, Physics and Pharmacy dominated the OA publications. Thus, it also indicates that science-based researchers are highly inclined towards publishing in OA as compared to non-science researchers. Top three OA journals in the list are Plos One (Multidisciplinary), Acta Chrystallographica Section E (Chemistry) and Electronic Journal of Geotechnical Engineering (Engineering, Geology). Most of the authors tend to publish in Quartile 3 journals (43%), followed by Q2 (28%), Q1 (16%) and Q4 (13%). However, with regard to citation impact per paper (average), every paper in Q1 journal received 6.25 citations, followed by Q2 (2.8 citations), Q3 (1.33 citations) and Q4 (0.87 citation). The APC range of OA publication found to be from RM0 to RM15, 000 per paper. The study provides useful insights about OA publication among USM researchers which can guide other researchers who wish to engage with OA in the future. Further study can be done by interviewing authors, to further explore on the OA research funding, strategy in choosing OA journals to publish in and also the motivation in publishing with OA.